2016
DOI: 10.1097/brs.0000000000001868
|View full text |Cite
|
Sign up to set email alerts
|

Does the Level of Cervical Disc Herniation Surgery Affect Performance-based Outcomes in National Football League Athletes?

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…From the initial 2,215 records identified, 495 duplicates were subsequently removed, and this left 1720 unique studies. After full text review, 13 articles 3,6,8,12,17,18,20,21,23,29,31,33,36 were determined to meet all inclusion criteria and subsequently used for data analysis, with a Cohen’s κ coefficient >0.8 between reviewers (Figure 1). See Table 1 for comprehensive demographics and major results from included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the initial 2,215 records identified, 495 duplicates were subsequently removed, and this left 1720 unique studies. After full text review, 13 articles 3,6,8,12,17,18,20,21,23,29,31,33,36 were determined to meet all inclusion criteria and subsequently used for data analysis, with a Cohen’s κ coefficient >0.8 between reviewers (Figure 1). See Table 1 for comprehensive demographics and major results from included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Mai et al 17 reported on single-level ACDF and PF outcomes in 40 NFL players for CDH. A total of 34 players underwent ACDF, and 23 (67.6%) returned to play for an average of 2.6 years postoperatively.…”
Section: Resultsmentioning
confidence: 99%
“…80,93 Adjacent segment degeneration occurred in 10% of players undergoing ACDF, while those treated with foraminotomy had an RTP rate of 92% and returned earlier than those with ACDF but had a 50% reoperation rate. 80…”
Section: Resultsmentioning
confidence: 99%
“…50,122 Players with cervical disc herniation may safely RTP, but RTP decreased to approximately 70% in those requiring anterior cervical discectomy and fusion (ACDF). 80,93 Adjacent segment degeneration occurred in 10% of players undergoing ACDF, while those treated with foraminotomy had an RTP rate of 92% and returned earlier than those with ACDF but had a 50% reoperation rate. 80…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation